Cabozantinib in Japanese patients with advanced hepatocellular carcinoma: Final results of a multicenter phase II study. Issue 5 (23rd January 2023) - Kato, Naoya; Kudo, Masatoshi; Tsuchiya, Kaoru; Hagihara, Atsushi; Numata, Kazushi; Aikata, Hiroshi; Inaba, Yoshitaka; Kondo, Shunsuke; Motomura, Kenta; Okano, Naohiro; Ikeda, Masafumi; Morimoto, Manabu; et al.
Abstract: Aim: Cabozantinib showed a favorable benefit–risk profile in Japanese patients with advanced hepatocellular carcinoma (HCC) in an open‐label, phase II study (NCT03586973). This analysis presents cumulative data to final database lock. Methods: Patients with previously treated, advanced HCC received cabozantinib 60 mg/day. Progression‐free survival (PFS) and tumor response rates in prior‐sorafenib and sorafenib‐naïve cohorts were assessed by independent radiology committee (IRC) and an investigator. Liver function was evaluated by albumin–bilirubin (ALBI) score. Results: Median cabozantinib exposure was 5.6 months. In the prior‐sorafenib cohort ( n  = 20), median PFS was 7.4 months per IRC assessment and 5.6 months per investigator assessment. In the sorafenib‐naïve cohort ( n  = 14), median PFS was 3.6 and 4.4 months per IRC and investigator assessment, respectively. Six‐month PFS rate per IRC and investigator assessment in the prior‐sorafenib cohort was 59.8% and 49.5%, respectively, and in the sorafenib‐naïve cohort was 16.7% and 35.7%, respectively. Disease control rate by both IRC and investigator assessment was 85.0% in the prior‐sorafenib cohort and 64.3% in the sorafenib‐naïve cohort. Median overall survival (Kaplan–Meier estimate) was 19.3 and 9.9 months in the prior‐sorafenib and sorafenib‐naïve cohort, respectively. Mean ALBI score remained relatively constant in patients able to continue treatment. The most frequent adverse events were palmar–plantar erythrodysesthesia syndrome, diarrhea, hypertension, and decreased appetite. No new safety concerns were identified. Conclusions: Cabozantinib showed efficacy and a manageable safety profile in Japanese patients with advanced HCC.